(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Extrapulmonary tuberculosis (EPTB) remains a major diagnostic challenge because of its paucibacillary nature, diverse clinical presentation, and difficulty in obtaining microbiological confirmation. Conventional culture-based drug susceptibility testing (DST), although considered the reference standard, is time-consuming and often delays initiation of appropriate therapy. Rapid molecular diagnostic techniques such as GeneXpert MTB/RIF and Line Probe Assay (LPA) have emerged as important tools for early diagnosis and detection of rifampicin resistance in tuberculosis. Aim: To evaluate the diagnostic performance of GeneXpert MTB/RIF and Line Probe Assay compared with conventional DST in extrapulmonary tuberculosis through a systematic review and meta-analysis. Materials and Methods: A systematic review and meta-analysis was conducted according to PRISMA guidelines. Electronic databases including PubMed, Embase, Scopus, Web of Science, Cochrane Library, and Google Scholar were searched for studies published between January 2010 and March 2025. Studies evaluating GeneXpert MTB/RIF and/or LPA in extrapulmonary tuberculosis specimens using conventional DST as the reference standard were included. Pooled sensitivity, specificity, diagnostic odds ratio (DOR), and summary receiver operating characteristic (SROC) curves were calculated using a random-effects model. Results: A total of 28 studies comprising 9,842 extrapulmonary specimens were included in the meta-analysis. The pooled sensitivity and specificity of GeneXpert MTB/RIF for detection of extrapulmonary tuberculosis were 83.4% (95% CI: 79.2–87.1%) and 96.8% (95% CI: 94.1–98.3%), respectively. The area under the SROC curve was 0.94. Subgroup analysis demonstrated highest sensitivity in lymph node aspirates (90.5%) and lowest sensitivity in pleural fluid specimens (52.3%). For rifampicin resistance detection, GeneXpert MTB/RIF showed pooled sensitivity and specificity of 91.2% and 98.5%, respectively. Line Probe Assay demonstrated pooled sensitivity of 88.7% (95% CI: 84.5–92.1%) and specificity of 99.1% (95% CI: 97.6–99.7%). Moderate heterogeneity was observed among included studies. Conclusion: GeneXpert MTB/RIF and Line Probe Assay demonstrate high diagnostic accuracy for rapid detection of extrapulmonary tuberculosis and rifampicin resistance compared with conventional DST. Although conventional culture-based DST remains the reference standard, molecular assays significantly reduce diagnostic delay and facilitate early initiation of appropriate therapy. Combined use of molecular diagnostics and conventional DST may improve management outcomes in extrapulmonary tuberculosis.